A handbook on aviation law - McKeegan, George; Ranieri, William (American Bar Association, Section of Litigation, 2017)
Whether discussing international or domestic air travel, this handbook is replete with interesting and provocative accident accounts and liability outcomes, many of which are the subject of significant court cases. This includes (but is not limited to) acts of terrorism, slip and falls on airport premises, baggage and cargo loss, cancellation and delay, refusal to transport, aircraft turbulence, communicable diseases, and more. The legal outcomes and rationales of these cases are included and explained.